Effect of Ba non-stoichiometry in Ba1-xZr0.1Ce0.7Y0.2O3-δ on its structure defect, sinterability and hydrogen permeability. Issue 11 (1st August 2020) - Zhang, Qiu-Yue; Han, Jiao-Jiao; Huang, Yao; Chen, Yan; Yan, Xi; Lang, Wan-Zhong
Abstract: Three powders of Ba0.95 Zr0.1 Ce0.7 Y0.2 O3-δ (BZCY095), BaZr0.1 Ce0.7 Y0.2 O3-δ (BZCY), Ba1.05 Zr0.1 Ce0.7 Y0.2 O3-δ (BZCY105) with different Ba contents were synthesized using solid state reaction method. The effects of Ba non-stoichiometry on structure defect, sinterability and hydrogen permeability were investigated in details. The results of XRD and SEM revealed that the excess of BaO (BZCY105) was beneficial to the formation of single phase and membrane sinterability, while the deficiency of BaO (BZCY095) was counterproductive because of the vaporization of BaO at high temperature. Moreover, according to XPS, EPR, FT-IR, Raman and UV–Vis analysis, BZCY105 contained more oxygen vacancies than BZCY095 and BZCY. Additionally, the hydrogen permeation flux through BZCY105 membrane was the highest one because excess BaO favors protonic and grain boundary conductivities. Finally, the mechanism of Ba non-stoichiometry in Ba1-x Zr0.1 Ce0.7 Y0.2 O3-δ was proposed. For BZCY105, the excess BaO might be substituted into Ce site to form more oxygen vacancies. As for BZCY095, the dopant of Y might tend to be substituted into Ba site, decreasing the concentration of oxygen vacancy.